HUBUNGAN ANTARA KEBIASAAN MEMBACA CERPEN DAN KETERAMPILAN MENULIS PUISI PADA SISWA SMA - Anggun Pertiwi; Abdussamad Abdussamad; Henny Sanuli (Universitas Tanjungpura, 2017)
Abstract Reading a literary product as short stories can add more vocabularies. Writing skill need creativity to use the vocabularies that they get from reading. This is a reason for the researcher to do analysis what is the relation between reading short stories with writing poem. This reasearch is to describing reading short stories habit, describing writing poem abilities, testing the relation between reading short stories habit and writing poem skill of grade X student SMA Negeri 5 Pontianak. The data taking of reading short stories habit using angket while the writing poem skill is taken by writing poem test. Based on the analysis of data in this research, it shows that the reading habit of grade X student of SMA Negeri 5 Pontianak is enough with 64,04%, and writing skill of grade X SMA Negeri 5 Pontianak is good with 71,31% and has linear relation Sig>0,05= 0,098>0,005. There also positive relation and significance between reading short stories with the result of writing poem Rh>Rt= (0,971>0,282). Based on the result, the reseacher hope that teacher will increase the habbit of reading short stories that still in enough categories to be good. Keywords: Reading Short Stories Habit, Writing Poem Skill, Relation Between Readingand Writing